Pretreatment Bonggol Jagung dengan Alkali Peroksida dan Hidrolisis Enzim - H. Maria Inggrid; Reinaldo Wong; Herry Santoso (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Corncobs are abundant lignocellulosic waste materials in Indonesia. Lignocellulosic biomass has the potential to be used as raw material to produce biofuel. Lignocellulosic material mainly consists of cellulose, hemicellulose and lignin. The convertion of lignocellulosic material to fermentable sugar involves pretreatment and  hydrolysis ( enzimatic saccharification ). The objective of this experiment is to optimize the operating condition of alkaline hydrogen peroxide pretreatment and enzimatic hydrolysis treatment to release fermentable sugar from corncob. In this experiment the effect of temperature and concentration of hydrogen peroxide ( H2O2) to lignin disruption by alkaline peroxide (AHP) pretreatment at pH 11.5 were studied. Under the optimum condition of alkaline hydrogen peroxide pretreatment ( 2% H2O2,  temperature of 35 oC,  pH 11.5, 12h )  and enzimatic hydrolysis treatment using cellusoft L. at 50 oC, pH 5, 12h, a total of 514.3 ppm glucose was obtained.